Framing the third cycling century. Bridging the gap between research and practice. - Grafl, Katherina; Bunte, Heike; Dziekan, Katrin; Haubold, Holger; Neun, Manfred (My University, 2018)
There is a tension between research and practice in the field of cycling as well as in general in environmental policy. Numerous scientific publications and knowledge do not reach the practitioners who might benefit from them. Not only was the International Cycling Conference 2017 intended to tackle this deficit with a large-scale forum, but also this publication, which takes up and continues the discussion started there. The innovative concept of the triad, consisting of scientists, practitioners and experts, produces new perspectives.
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Verkehrssicherheit; Nachhaltigkeit; Kommunikation; GPS; Gesundheit; Elektromobilität; Radverkehrspolitik; Radverkehrssicherheit; Radfahren; Radverkehrsförderung; Lastenrad; Cargobike